Epistemologies of Rebellion: The Tricolor Cockade and the Problem of Subaltern Speech. (December 2015) - Olson, Kevin
This essay follows Michel Foucault's inspiration to develop an archaeology of subaltern politics. In the archives left from the Haitian Revolution, we find occasional references to slaves wearing the tricolor cockade, the famous symbol of French republicanism. The archives are silent on what wearing the cockade "meant, " however, or why whites found it so threatening. Rich layers of meaning are packed into these silences. They reveal a great deal about the performative character of the public sphere and the epistemological complexity of mixing race with revolutionary politics. Wearing the cockade was a screen of projection for all kinds of ideas, including the paranoid fears and guilty conscience of white slaveholders. It probed tensions implicit within Enlightenment colonialism, making those tensions explicit to white elites. By eliciting this self-critical response, the cockade served as a disruptive enigma well suited to the critical and political needs of people not allowed to speak.